(untitled) (Journal of Engineering, 2024)
Thermal buckling analysis of symmetric and antisymmetric cross-ply laminated hybrid composite plates with an inclined crack subjected to a uniform temperature rise are presented in this paper. The first-order shear deformation theory in conjunction with variational energy method is employed in the mathematical formulation. The eight-node Lagrangian finite element technique is used for obtaining the thermal buckling temperatures of hybrid composite laminates. The effects of crack size and lay-up sequences on the thermal buckling temperatures for symmetric and a antisymmetric plates are investigated. The results are shown in graphical form for various boundary conditions. Finally, from this paper, the following main results have been found from which the buckling temperature is affected the larger crack length more than the small crack length, together with other result that the buckling temperature of the plate for every perforation angle is to increase while crack length is increasing.